Sources of poetry by Konstancja Benisławska. Baroque penitential elegy and “Songs Sung to Oneself” - Żukowska, Kamila (Melusine. Old Literature and Culture, 2026)
The article is devoted to the analysis of the religious model present in „Songs Sung to Oneself ” by Konstancja Benisławska, an eighteenth-century poet from Polish Livonia. Benisławska’s work, interpreted by Marek Prejs as a „manifestation of conscious historicism”, has not yet received research focusing on its possible Baroque sources and inspirations, among which the penitential elegy popular in the 17th century was undoubtedly present. The genre in which the lyrical ego assumes the costume of David’s penitential attitude, is characterized by penetrating contents contained in existential anxiety and high temperature of the emotions while stressing such traits as the impermanence and ridicule of human intentions. These elements also appear in Benisławska’s work. Therefore, the poet’s work can be perceived as a continuation of the tradition of penitential elegy, present mainly in the texts of seventeenth-century poets, as: Kasper Miaskowski, Wacław Potocki or Wespazjan Kochowski.